2008
DOI: 10.1016/j.yexcr.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-124 regulates neurite outgrowth during neuronal differentiation

Abstract: MicroRNAs (miRNAs) are small RNAs with diverse regulatory roles. The miR-124 miRNA is expressed in neurons in the developing and adult nervous system. Here we show that overexpression of miR-124 in differentiating mouse P19 cells promotes neurite outgrowth, while blocking miR-124 function delays neurite outgrowth and decreases acetylated α-tubulin. Altered neurite outgrowth also was observed in mouse primary cortical neurons when miR-124 expression was increased, or when miR-124 function was blocked. In uncomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
211
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(225 citation statements)
references
References 89 publications
12
211
0
Order By: Relevance
“…miRNAs play very important roles in many aspects of neuronal function and in a variety of physiological processes in the central nervous system (CNS) (14). For instance, miRNAs are implicated in neurite outgrowth (15,16), regulate dendritic spine development (17), promote neurogenesis in the midbrain-hindbrain domain (18), and control human neuronal differentiation (19). Overexpression of a single miRNA can even shift the overall gene expression profile of a cell from nonneuronal to neuronal (20).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…miRNAs play very important roles in many aspects of neuronal function and in a variety of physiological processes in the central nervous system (CNS) (14). For instance, miRNAs are implicated in neurite outgrowth (15,16), regulate dendritic spine development (17), promote neurogenesis in the midbrain-hindbrain domain (18), and control human neuronal differentiation (19). Overexpression of a single miRNA can even shift the overall gene expression profile of a cell from nonneuronal to neuronal (20).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…For instance, miR-124 can inhibit SCP1 expression in embryonal carcinoma cell P19 and shows a complementary expression pattern during spinal cord development [6]. Overexpression of miR-124 in P19 cells contributes to the control of neurite outgrowth by regulation of the cytoskeleton remodeling [7]. In the mouse neuroblastoma cell lines, CAD and Neuro2a, miR-124 promotes the differentiation by targeting PTBP1 mRNA encodes a Abbreviations: miRNA, microRNA; AHR, aryl hydrocarbon receptor; 3 0 -UTR, 3 0 -untranslated mRNA region; Pre, pre-miR-124 precursor; Inh, anti-miR-124 miRNA inhibitor; Mock-Pre, precursor negative control; Mock-Inh, inhibitor negative control global repressor of alternative pre-mRNA splicing in nonneuronal cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs are known to be associated with the nervous system, of which miR-124 is by far the most abundantly expressed (Kosik 2009;Lagos-Quintana et al 2002). Although several studies have suggested important roles of miR-124 in various aspects of neural development, including neurogenesis, neuronal differentiation and neurite outgrowth (Åkerblom et al 2012, Cheng et al 2009, Yu et al 2008, its physiological significance has remained controversial to date, since others have doubted its essential function in neural development (Cao et al 2007). However, several direct miR-124 targets have been identified that possibly account for its putative role in neural development, including the small GTPase Rho kinase Rock1.…”
Section: Discussionmentioning
confidence: 99%
“…Results from mice carrying conditional null mutations for dicer, an enzyme required for the cleavage of pre-miRs into mature miRs (Bernstein et al 2001), indicate the essential role of miRNAs in many cellular processes (Cuellar et al 2008;Davis et al 2011;Harris et al 2006;Harfe et al 2005;Nagalakshmi et al 2011). MicroRNAs are believed to contribute to the specification and differentiation of various cell types including neurons (Åkerblom et al 2012;Yu et al 2008;Stappert et al 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation